2020
DOI: 10.1186/s12916-020-01598-7
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in analysing and reporting binary outcome data—a review of randomised controlled trial reports

Abstract: Background Randomised controlled trials (RCTs) need to be reported so that their results can be unambiguously and robustly interpreted. Binary outcomes yield unique challenges, as different analytical approaches may produce relative, absolute, or no treatment effects, and results may be particularly sensitive to the assumptions made about missing data. This review of recently published RCTs aimed to identify the methods used to analyse binary primary outcomes, how missing data were handled, and how the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In this secondary data analysis, the reporting of the binary outcome is confined by the data type collected in the pre-defined assessment tool. In order to remedy the shortcomings in reporting binary outcomes, Rombach and colleagues [ 60 ] recommended medical researchers to use statistical methods that could quantify the confidence intervals of the primary binary outcomes whenever available (including logistic regression in our study), instead of choosing analysis method that could only produce a corresponding p -value (such as chi-square test).…”
Section: Discussionmentioning
confidence: 99%
“…In this secondary data analysis, the reporting of the binary outcome is confined by the data type collected in the pre-defined assessment tool. In order to remedy the shortcomings in reporting binary outcomes, Rombach and colleagues [ 60 ] recommended medical researchers to use statistical methods that could quantify the confidence intervals of the primary binary outcomes whenever available (including logistic regression in our study), instead of choosing analysis method that could only produce a corresponding p -value (such as chi-square test).…”
Section: Discussionmentioning
confidence: 99%
“…Six review articles describing the handling of missing data in RCTs found that only 22% of the 649 trials reviewed reported some kind of sensitivity analysis. [13][14][15][16][17][18] The majority retained the missingness assumptions of the original analysis, with only a small subset relaxing the original assumptions, and almost none considering a MNAR mechanism. 13 Applying sensitivity analyses can be limited by the complexity of the methods, and a lack of transparency about the assumptions underlying each method.…”
Section: Discussionmentioning
confidence: 99%
“…In the broader context of selection models in general, Copas and Jackson 7 defined a bias limit, which is equivalent to the maximum CCA estimator bias that we derive here (15). We extend Copas and Jackson's bias limit to the TM estimator, and define the maximum possible TM bias, which, for the case of lower value trimming, occurs under highest value dropout.…”
Section: The Strong Mnar Assumptionmentioning
confidence: 92%
“…and M.Y.) trained in medical statistics with reference to Consolidated Standards of Reporting Trials (CONSORT) [17] and the other methodological studies [18][19][20][21]. Subsequently, they discussed with two experienced methodologists (L.L.…”
Section: Data Collectionmentioning
confidence: 99%